1989
DOI: 10.1111/j.1365-2184.1989.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian synchronization of liver regeneration in adult rats: the role played by adrenal hormones

Abstract: The role played by the adrenal hormones in the regulation of liver proliferation in adult rats was investigated under various experimental conditions.In untreated control groups, cell growth was very low and endogenous corticosterone levels showed a clearly-defined circadian rhythm with a peak in the evening. Adrenalectomy depressed the level of endogenous corticosterone immediately and the growth rate of the liver increased significantly. We were able to prevent this effect by repeated injections of corticost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The importance of portal venous blood flow to basal hepatocyte proliferation is clear, however, as evidenced by the hepatic atrophy that occurs when portal blood flow is absent [6,7]. Additionally, circadian peaks of DNA synthesis occur postprandially, during times of peak portal venous blood flow [8,9].…”
Section: Mature Hepatocyte Replicationmentioning
confidence: 98%
“…The importance of portal venous blood flow to basal hepatocyte proliferation is clear, however, as evidenced by the hepatic atrophy that occurs when portal blood flow is absent [6,7]. Additionally, circadian peaks of DNA synthesis occur postprandially, during times of peak portal venous blood flow [8,9].…”
Section: Mature Hepatocyte Replicationmentioning
confidence: 98%
“…A circadian rhythm of liver regeneration exists [14,82] e.g. the induction of liver regeneration by various hepatotoxins should preferentially be initiated at a standardized time of day (between 9:00 and 12:00 in the morning).…”
Section: Working 9 To 12?mentioning
confidence: 99%
“…Barbason et al (Barbason et al, 1989) have previously demonstrated that, following partial hepatectomy, the number of mitotic cells in the liver showed daily fluctuations from high levels during the early day to lower levels at night. During mitosis, transcription is almost completely suppressed, which may contribute to the overall decrease in gene expression.…”
Section: Discussionmentioning
confidence: 98%